The effect of short-term practice of mindfulness meditation in alleviating stress in university students - Myint, K.; Choy, K.L.; Tin, Tin Su; Lam, S.K. (2011)
Although mindfulness meditation practice appears to confer positive effects on various clinical conditions, physiological responses to this practice in healthy individuals are largely unknown. This study is aimed at evaluating the physiological effects of short-term mindfulness meditation in university students intending to take a written term examination. Young healthy university students (n=18) recruited as participants were divided equally into a meditation group without examination stress, a non-meditating group with examination stress, and a meditation group with examination stress. The meditation intervention groups were offered mindfulness practice twice daily of 1 h each time for a period of 5 weekdays, except for weekends, for 3 consecutive weeks. The parameters measured included heart rate, blood pressure and serum cortisol. Depression Anxiety Stress Scales (DASS) were also obtained to monitor any negative psychological symptoms. All parameters were measured before intervention, just after intervention, which also coincided with the eve of the academic examination and at 3 weeks after. The DASS-Stress scale was significantly (p<0.05) reduced after intervention in the meditation group with no examination challenge. However, no significant changes were found in the cardiovascular and cortisol outcomes amongst all groups for all time lines. Even though these findings did not show any significant physiological responses to the short-term mindfulness practice in stressful conditions, nonetheless, the results demonstrate the potential benefits of this practice in alleviating stress in the neutral environment of university students. Future studies should address the effects of mindfulness practice in larger groups exposed in stressful situations.